The Palgrave Handbook of Screenwriting Studies - Davies, Rosamund; Russo, Paolo; Tieber, Claus (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
XLI, 818 p. 39 illus., 16 illus. in color.